Can 8 weeks of training in female swimmers affect active drag? - Marinho, D. A.; Garrido, N.; Barbosa, T. M.; Reis, V. M.; Silva, A.J.; Costa, A. M.; Marques, M. C. (The Open Sports Sciences Journal, 2010)
Hydrodynamic drag is the force that a swimmer has to overcome in order to maintain his movement through water and is influenced by velocity, shape, size and the frontal surface area Thus, the aim of this study was to assess the effects of 8 weeks of training on active drag in young female swimmers. 8 female age group swimmers belonging to the same swimming club participated in this study. Active drag measurements were conducted in two different trials: at the beginning of the season and after 8 weeks of training. The velocity perturbation method was used to determine active drag in front crawl swimming. After 8 weeks of training, mean active drag decreased, although no significant differences were found between the two trials. No significant differences were observed in swimming velocity between the two trials. It seems that 8 weeks of swimming training were not enough to allow significant improvements on swimming technique. One can recommend that specific training sets concerning technique correction and improvement in young swimmers should be a main aim during training planning.